Infant mortality in a very low birth weight cohort from a public hospital in Rio de Janeiro, RJ, Brazil - Regina Coeli Azeredo Cardoso; Patrícia Viana Guimarães Flores; Cláudia Lima Vieira; Kátia Vergetti Bloch; Rejane Sobrino Pinheiro; Sandra Costa Fonseca; Claudia Medina Coeli (Instituto Materno Infantil de Pernambuco, 2013)
OBJECTIVES: to evaluate infant mortality in very low birth weight newborns from a public hospital in Rio de Janeiro, Brazil (2002-2006). METHODS: a retrospective cohort study was performed using the probabilistic linkage method to identify infant mortality. Mortality proportions were calculated according to birth weight intervals and period of death. The Kaplan-Meier method was used to estimate overall cumulative survival probability. The association between maternal schooling and survival of very low birth weight infants was evaluated by means of Cox proportional hazard models adjusted for: prenatal care, birth weight, and gestational age. RESULTS: the study included 782 very low birth weight newborns. Of these, (28.6%) died before one year of age. Neonatal mortality was 19.5%, and earlyneonatal mortality was 14.9%. Mortality was highest in the lowest weight group (71.6%). Newborns whose mothers had less than four years of schooling had 2.5 times higher risk of death than those whose mothers had eight years of schooling or more, even after adjusting for intermediate factors. CONCLUSIONS: the results showed higher mortality among very low birth weight infants. Low schooling was an independent predictor of infant death in this low-income population sample.